PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA GAMBAR TEKNIK PADA SISWA KELAS XIAV4 DI SMKN 3 WONOSARI - Wiryatun Wiryatun (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
This study aims to improve the ability of understanding the engineering sketch among student of class XI AV4 SMK Negeri 3 Wonosari (vocational high school) by applying guided inquiry model. This action class research used descriptive statistical approach. This study conducted in two cycle, with 4 component in each cycle, i.e. planning, action, observation, and reflection. Subject of the study were 32 students. Instruments of this study were teacher activity observation sheet, student activity observation sheet, and assessment sheet of understanding the engineering sketch. Results of the study reveal 1) the improvement of teacher and student activity during the learning procces, 2) the improvement of student activity, and 3) the improvement of student’s ability in understanding the engineering sketch. The teacher activity in cycle I was 64% (bad category) then increased to 88% (good category) in cycle II. The student activity in cycle I was 71 (good category) then increased to 87% (excellent category) in cycle II. The student abillity to understanding the engineering sketch also improve from 31% before the cycles, became 56.25% in cycle I, and further increased to 87.5% and in cycle II. It can be concluded from the study that guided inquiry model may improve the ability of understanding the engineering sketch among student of class XI AV4 SMK Negeri 3 Wonosari, both in the individual and classical completeness.